US tax policy and health insurance demand: Can a regressive policy improve welfare? - Karsten Jeske; Sagiri Kitao (Federal Reserve Bank of Atlanta, 2007)
The U.S. tax policy on health insurance is regressive because it favors only those offered group insurance through their employers, who tend to have a relatively high income. Moreover, the subsidy takes the form of deductions from the progressive income tax system, giving high-income earners a larger subsidy. To understand the effects of the policy, we construct a dynamic general equilibrium model with heterogenous agents and an endogenous demand for health insurance. We use the Medical Expenditure Panel Survey to calibrate the process for income, health expenditures, and health insurance offer status through employers and succeed in matching the pattern of insurance demand as observed in the data. We find that despite the regressiveness of the current policy, a complete removal of the subsidy would result in a partial collapse of the group insurance market, a significant reduction in the insurance coverage, and a reduction in welfare coverage. There is, however, room for raising the coverage and significantly improving welfare by extending a refundable credit to the individual insurance market.
Keywords: E21; E62; I10; 330; health insurance; risk sharing; tax policy; adverse selection